PENERAPAN MODEL PEMBELAJARAN ACTIVE LEARNING DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN AQIDAH AKHLAK DI MTs. ALKHAIRAAT MADINATUL ILMI DOLO - Yudianto, Ahmad (Scolae: Journal of Pedagogy, 2023)
This research discusses the implementation of the Active Learning model in improving students' learningoutcomes in the subject of Islamic faith and morals at MTs Alkhairaat Madinatul Ilmi, Dolo District, Sigi Regency. Themain issues addressed in this thesis are: How is the implementation of the Active Learning model in the subject ofIslamic faith and morals? What steps are used in implementing the Active Learning model in the subject of Islamic faithand morals? What are the obstacles and solutions to the Active Learning model in the subject of Islamic faith andmorals?The research approach is qualitative, employing data collection techniques such as observation, interviews,documentation, followed by data reduction, data presentation, and verification through triangulation methods.The results of this thesis research indicate that the implementation of the Active Learning model greatlyassists educators and students in the teaching and learning process. Students are encouraged to create an atmospherewhere they actively ask questions, inquire, and develop ideas, thereby becoming the center of learning activities.Educators act as facilitators, motivators, and inspirators, controlling, supervising, and providing opportunities forstudents to think critically, develop inspiration, and creativity. The implementation involves designing learningactivities, motivating students, organizing them, and presenting the material. Challenges in implementing the ActiveLearning model include students' lack of confidence and limited time allocation, while solutions involve motivatingstudents and training them to articulate thoughts and manage time effectively.